2013
DOI: 10.1111/ctr.12091
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of antithymocyte globulin in patients with hematological malignancies undergoing myeloablative allogeneic hematopoietic cell transplantation: a systematic review and meta‐analysis

Abstract: Antithymocyte globulin (ATG) has shown efficacy in preventing acute GVHD (aGVHD) in allogeneic hematopoietic cell transplantation (allo-HCT), but its efficacy in chronic GVHD (cGVHD) and long-term outcomes remains controversial. We conducted a systematic review and meta-analysis to evaluate potential benefit and risk of prophylactic ATG use in myeloablative HCT. We searched Pubmed, EMBASE, Cochrane databases, and included 10 trials (two RCTs and eight retrospective) comparing ATG use vs. control with a total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…On the other hand, antithymocyte globulin (ATG) has been used as an effective prophylactic agent against GVHD despite concerns of increased risk of relapse or lethal infections . Our previous study, which compared the outcomes of transplants from HLA‐mismatched unrelated donor (URD) with and without low‐dose rabbit ATG (1.25 mg/kg for 2 d), reported a lower incidence of GVHD without increased relapse and infectious complications, which was translated to a lower incidence of non‐relapse mortality (NRM) and survival benefits in the ATG group .…”
mentioning
confidence: 99%
“…On the other hand, antithymocyte globulin (ATG) has been used as an effective prophylactic agent against GVHD despite concerns of increased risk of relapse or lethal infections . Our previous study, which compared the outcomes of transplants from HLA‐mismatched unrelated donor (URD) with and without low‐dose rabbit ATG (1.25 mg/kg for 2 d), reported a lower incidence of GVHD without increased relapse and infectious complications, which was translated to a lower incidence of non‐relapse mortality (NRM) and survival benefits in the ATG group .…”
mentioning
confidence: 99%
“…Better GvHD prevention, even if this does not significantly improve OS, may still be a reasonable approach, which was shown by the results regarding GRFS. Interestingly, based on previous reports, [3][4][5][27][28][29][30] Shin et al 31 applied a risk-adapted GvHD prophylaxis strategy for patients receiving HLA-matched UD transplants, which involved adding low-dose rabbit ATG to the conditioning regimen in transplants using PBSC, but not BM. They report a similar outcome, including a comparable incidence of GvHD between the BM and PBSC groups.…”
Section: Discussionmentioning
confidence: 99%
“…Toward this goal, several clinical studies to-date have shown that the depletion of T lymphocytes with antithymocyte/antilymphocyte globulin can be very effective at preventing moderate-to-severe chronic GVHD after transplantation from an unrelated donor [150][151][152][153][154]. Toward this goal, several clinical studies to-date have shown that the depletion of T lymphocytes with antithymocyte/antilymphocyte globulin can be very effective at preventing moderate-to-severe chronic GVHD after transplantation from an unrelated donor [150][151][152][153][154].…”
Section: Mobilized Peripheral Bloodmentioning
confidence: 99%